Struktur analysis and material selection in reactor and condensers for liquid smoke maker - Saefuloh, Iman; Pangestu, Rizky Abi; Sudrajad, Agung (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Liquid smoke can be obtained by condensing or condensing biomass from the pyrolysis process . To make a liquid smoke device, an appropriate material is needed because the resulting liquid smoke will function as food preservation, especially for milkfish preservation. Therefore we need a suitable material so as not to affect the results of the liquid smoke. On the other hand, structural analysis is also needed to determine the strength of the material in this liquid smoke maker. The first method used is a qualitative method. This method is a computational method using software that has been developed by Ashby named CES Edupack. The second method is used for selecting the next material, quantitative method is a systematic method used to narrow the choice of material with themethod approach digital logic. In the research results, the selected material is Stainless Steel 304 with specifications Thermal Conductivity: 16.2 (W / mK) Maximal Service Temperature: 750 (oC) Density: 8 (g / cc) Yield Strength: 215 (Mpa). With the analysis of the structure, namely the condenser maximum stress is 2x104 N / m2, for the Strain the value is 6.08x10-9 . for Displacement, it can be 3 x 10 -5 mm. The safety factoris 1 x 10 6. obtainedFor the tangential stress obtained is 11.05 N / m2. At the maximum strain reactor is 321 MPa, the strain resultingis 8x10-6 . For the displacement , the result is 0.09 mm. and the last is the safety factor , the result is 65. For the longitudinal stress that is produced is 1.65 N / m2